2010
DOI: 10.1186/1471-2164-11-230
|View full text |Cite
|
Sign up to set email alerts
|

Whole transcriptome analysis of the hippocampus: toward a molecular portrait of epileptogenesis

Abstract: BackgroundUncovering the molecular mechanisms involved in epileptogenesis is critical to better understand the physiopathology of epilepsies and to help develop new therapeutic strategies for this prevalent and severe neurological condition that affects millions of people worldwide.ResultsChanges in the transcriptome of hippocampal cells from rats subjected to the pilocarpine model of epilepsy were evaluated by microarrays covering 34,000 transcripts representing all annotated rat genes to date. Using such gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
75
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(81 citation statements)
references
References 43 publications
6
75
0
Order By: Relevance
“…After phosphorylation, STATs dimerize and translocate to the nucleus, where they bind specific regions to promote relative genes transcription [5]. Based on previous reports linking gliosis to STAT3 activation in glioblastoma [12] and the role of STAT3 in epileptogenesis [11], we here tested the hypothesis that p-STAT3 increases GFAP after epilepsy and that STAT3 activation contributes to reactive gliosismediated epileptogenesis. Our patients data demonstrate the up-regulation of p-STAT3 and GFAP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After phosphorylation, STATs dimerize and translocate to the nucleus, where they bind specific regions to promote relative genes transcription [5]. Based on previous reports linking gliosis to STAT3 activation in glioblastoma [12] and the role of STAT3 in epileptogenesis [11], we here tested the hypothesis that p-STAT3 increases GFAP after epilepsy and that STAT3 activation contributes to reactive gliosismediated epileptogenesis. Our patients data demonstrate the up-regulation of p-STAT3 and GFAP.…”
Section: Discussionmentioning
confidence: 99%
“…For Zucai Xu and Tao Xue are equal to this article. example, STAT3 could be activated in the brain by specific triggers, such as cerebral ischemia, inflammatory stimulation, epilepsy [8][9][10][11]. Moreover, recent in vivo reports have revealed that STAT3 plays a central role in astrocyte proliferation and p-STAT3 regulates reactive astrogliosis (and GFAP expression) after CNS injury [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…These include involvement of proteolytic cascades (Gorter et al 2007), transforming growth factor b (TGF-b) and insulin-like growth factor 1 (IGF-1) signaling (Cacheaux et al 2009), p38MAPK, Jak-STAT, PI3K, mammalian target of rapamycin (mTOR) (Okamoto et al 2010), complement activation , and gene expression modulation related to glial oxidative stress and synaptic vesicle trafficking in epileptogenesis (Winden et al 2011). An obvious question related to changes in the transcriptome is: What controls gene expression?…”
Section: Molecular Mechanisms Of Epileptogenesismentioning
confidence: 99%
“…Concerning the cellular and molecular processes that may be regulated by mTORC1 in the CNS, pharmacological modulation of the mTOR signaling pathway could be a promising alternative in different neurological disease therapies, such as in epilepsy treatment (Lipton and Sahin, 2014). In agreement, hyperactivation of mTOR signaling is evident in models of acute seizure (Zhang and Wong, 2012), status epilepticus (Okamoto et al, 2010), and epileptic patients (Berdichevsky et al, Fig. 1.…”
Section: Discussionmentioning
confidence: 82%